Investigation on the performance of blake hydraulic ram pump - Charl Dawin Reson (2022)
his research involves the development of a ram pump that can pump water without the need for external energy sources. It is deemed an important analysis because, once completed, it can be utilised to improve and facilitate various agriculture and health-related activities. Prior research has been conducted on the ram pump. However, the purpose of this study is to comprehend the prototype built system in order to determine the optimal combination of parameters that will result in changing their performance of the ram pump system. The investigation will be conducted by reviewing scientific literature and developing a hydraulic ram pump prototype and testing it using an experimental procedure. In order to decide if it is worthwhile to put a ram pump in specific locations, it is necessary to have a thorough understanding of the advantages and disadvantages of the ram pump, which encompasses both the experimental and literary fields. As a result of this investigation, the Blake Hydraulic Ram Pump's operating parameters have been determined. Higher mass added to waste valves doesn't increase the system's performance, as it is shown that the hydraulic ram pump reaches its highest peak of performance at a certain mass level, although it must be taken into account that the mass added and the length of the lifting stroke of the waste valve can be controlled in this system, as it affects the working rhythm of the pump. When the waste valve is fully open, the pump performs better, as long as it is running at a high lifting stroke.